Czy podejście hermeneutyczne jest interpretacyjnym wytrychem? Diagnoza i propozycja w kontekście współczesnej prozy - Szkaradnik, Katarzyna (Przestrzenie Teorii, 2019)
The paper is an attempt to reflect on whether hermeneutics can still be a cognitively fruitful approach in literary studies, especially in respect of contemporary output. The authoress analyses two currents in the literature, which could be named integrating and eristic. They seem to correspond with two paradigms in hermeneutics: affirmative, concentrating on “brightening an existence”, and radical, emphasizing “weakness”, “flux”, “collapsing” etc. A key issue is the doubt whether applying the name “hermeneutics” is not in itself misleading, as it concerns diametrically opposed points of view. The authoress proposes her own understanding of hermeneutics as a perspective of reading literature, which “cling on” to the protagonists’, author’s and interpreter’s experience. She also invokes the metaphors of scaffolding and house building, where the home is marked with an unrelenting “uneasiness” and lacks strong foundations, but does convey the situation of incessant common constructing the accidental and demanding protection of meaning.